Shallot-Peel Extract Supplementation Increases Glutathione Levels in Gastritis Rat Model - Febianti, Zahrah; Utama, Bagas Wahyu; Handoko, Adelia (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Mefenamic acid can cause gastritis. Glutathione is one of the oxidative stress defense mechanisms and nutrient supplementation containing high antioxidants. Peel of shallot (Allium cepa var. Ascalonicum) contains higher antioxidant compounds and may increase glutathione levels. This study aimed to analyze the effect of shallot peel extract supplementation on gastric glutathione (GSH) levels in gastritis rats model.Methods: This was an experimental study using 24 male Wistar rats which were divided into 4 groups, namely group K0 (given 2 ml of aquadest for 14 days); group K1 (given mefenamic acid 23.25 mg/day for the first 7 days, then Na-CMC 2 ml/day for the next 7 days), group P1 and P2 (given mefenamic acid 23.25 mg/day for the first 7 days, then given shallot peel extract for the next 7 days at dose of 600 mg/kgBW/day or 1200 mg/kgBW/day). Gastric GSH levels were determined by the Ellman method. The data was analyzed by ANOVA and post hoc test.Results: The shallot peel extract supplementation at a dose of 600 mg/kgBW and 1200 mg/kgBW significantly increased gastric GSH levels in gastritis rats (p<0.05), however, GSH levels did not reach normal conditions. Linear regression analysis showed an R coefficient of 0.751.Conclusion: Shallot peel extract supplementation increases gastric GSH levels in gastritis rats model in a dose-dependent manner, suggesting an effective dose of shallot peel extract. Further study to develop shallot peel extract into phytopharmaca is imperative.